I might be a liar, but not a thief: An experimental distinction between the moral costs of lying and stealing - Daniel Hermann; Oliver Mußhoff (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2018)
In this paper, we shed light on the different moral costs of dishonesty and stealing. To accomplish this, we set up a die-rolling task which allowed participants to increase their own payout through dishonesty or theft. The results show that participants have fewer reservations about dishonesty compared to stealing, which implies higher intrinsic costs for stealing. We found that gender contributes to this effect, as women distinguish significantly between lying and stealing, while men do not.
Keywords: C91; D63; D82; 330; Lying; Deception; Stealing; Laboratory Experiment; Behavioral Economics